2020
DOI: 10.1017/s204017442000015x
|View full text |Cite
|
Sign up to set email alerts
|

Can measurement of the foetal renal parenchymal thickness with ultrasound be used as an indirect measure of nephron number?

Abstract: Chronic kidney disease continues to be under recognised and is associated with a significant global health burden and costs. An adverse intrauterine environment may result in a depleted nephron number and an increased risk of chronic kidney disease. Antenatal ultrasound was used to measure the foetal renal parenchymal thickness (RPT), as a novel method to estimate nephron number. Foetal renal artery blood flow was also assessed. This prospective, longitudinal study evaluated the foetal kidneys of 102 appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The return of kidney function may correlate with nephron mass, as determined by cortical thickness. 15 , 16 Renal biopsy has been used by Huang et al 17 to predict the ability of the recovery. Sclerotic glomeruli was found to be associated with severe injury of the kidney and reduction in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The return of kidney function may correlate with nephron mass, as determined by cortical thickness. 15 , 16 Renal biopsy has been used by Huang et al 17 to predict the ability of the recovery. Sclerotic glomeruli was found to be associated with severe injury of the kidney and reduction in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that measuring only the renal parenchyma has less variance than renal volume and appears to be a more accurate method to estimate nephron number. 16,17 There are currently, to our knowledge, no studies comparing renal parenchymal growth between preterm delivered infants and undelivered normally grown fetuses who would be expected to achieve optimal renal parenchymal growth and ideal nephron endowment.…”
Section: Introductionmentioning
confidence: 99%
“…Bennet et al 3 review the current state of art in the development of radiological tools for ex vivo and in vivo assessment of nephron number and glomerular size. Brennan et al investigate the use of ultrasound based fetal renal parenchymal thickness (RPT) as a novel non-invasive marker of nephron endowment 4 . The authors show that fetal RPT can be used to track the effects of fetal growth restriction on kidney development in utero.…”
mentioning
confidence: 99%